2013
DOI: 10.1148/radiol.13122276
|View full text |Cite
|
Sign up to set email alerts
|

Contrast Material–induced Nephrotoxicity and Intravenous Low-Osmolality Iodinated Contrast Material: Risk Stratification by Using Estimated Glomerular Filtration Rate

Abstract: Purpose:To determine the effect of intravenous (IV) low-osmolality iodinated contrast material (LOCM) on the development of post-computed tomography (CT) acute kidney injury (AKI), stratified by pre-CT estimated glomerular filtration rate (eGFR), in patients with stable renal function. Materials and Methods:Institutional review board approval was obtained and patient consent waived for this HIPAA-compliant, retrospective study. CT examinations performed over a 10-year period on unique adult inpatients with suf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
233
1
11

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 332 publications
(256 citation statements)
references
References 25 publications
3
233
1
11
Order By: Relevance
“…Recent data show that CIN is rarely seen in patients with an estimated glomerular filtration rate (eGFR) greater than 45 ml/min/1.73m 2 , although stage IV and V chronic kidney disease is one of the main risk factors for the development of CIN. 1,5,6 Other risk factors for CIN include: diabetes; congestive heart failure; age over 70 years; hypovolemia; concomitant use of nephrotoxic agents and non-steroidal anti-inflammatory drugs.…”
Section: Contrast Induced Nephropathymentioning
confidence: 99%
“…Recent data show that CIN is rarely seen in patients with an estimated glomerular filtration rate (eGFR) greater than 45 ml/min/1.73m 2 , although stage IV and V chronic kidney disease is one of the main risk factors for the development of CIN. 1,5,6 Other risk factors for CIN include: diabetes; congestive heart failure; age over 70 years; hypovolemia; concomitant use of nephrotoxic agents and non-steroidal anti-inflammatory drugs.…”
Section: Contrast Induced Nephropathymentioning
confidence: 99%
“…Therefore, MEI+ images at 40 keV could be regarded as ideal for the depiction of intrahepatic vessels [17]. Furthermore, this algorithm-based post-processing is a promising candidate for calculated saving of contrast media, from which patients with reduced kidney function might benefit [3,4,18,19]. These improved post-processing capabilities at low virtual keV values might also increase the sensitivity for the detection of soft-tissue lesions, e. g. in melanoma.…”
mentioning
confidence: 99%
“…Most studies found no difference in the incidence of AKI among matched patients. Subgroup analyses based on baseline kidney function also did not show any differences, except for the study by Davenport that found a higher AKI incidence after contrast in advanced chronic kidney disease (CKD) [3]. McDonald found a greater need for dialysis in ICU patients with pre-CT eGFR ≤ 45 ml/l/BSA (6.7% vs 2.5%; OR 2.72 (1.44-6.46), however, without impact on the AKI creatinine criterion [4].…”
Section: Consistencymentioning
confidence: 90%